The Interconnection between Religion and Profane World: The Role of Religious Leaders in Enforcing Human Rights - Wibowo, Antonia Rahayu Rosaria (Center for Research and Development of Religious Literature and Heritage, 2025)
The Document on Human Fraternity for World Peace and Living Together emerged from a 2019 meeting between Pope Francis and the Grand Imam of Al-Azhar, Ahmad al-Tayyeb, in Abu Dhabi. Motivated by deep concern over global suffering and crises, the two religious leaders sought to articulate a vision of unity and peace. Decades earlier, in 1948, the United Nations General Assembly adopted the Universal Declaration of Human Rights (UDHR) in response to the aftermath of World War II. Although separated by 71 years, these two documents share fundamental connections. This article explores the intersection of religion and the secular realm, as demonstrated by these texts. A comparative examination highlights the significant role of religious leaders in advocating for human rights beyond theological contexts. The study draws on desk research, incorporating primary data from both documents and secondary sources from academic journals and international organizations. Paul Ricoeur's hermeneutics approach was applied to analyze their themes and implications. Findings reveal two key points of convergence. First, both documents emphasize seven types of human rights. Second, religious and world leaders express a shared commitment to peace and the protection of human dignity. The role of religious figures in human rights enforcement is evident in their call for collective action, urging believers to unite against injustice and wrongdoing.